If it's not what You are looking for type in the equation solver your own equation and let us solve it.
56=3m+2(m+3)
We move all terms to the left:
56-(3m+2(m+3))=0
We calculate terms in parentheses: -(3m+2(m+3)), so:We get rid of parentheses
3m+2(m+3)
We multiply parentheses
3m+2m+6
We add all the numbers together, and all the variables
5m+6
Back to the equation:
-(5m+6)
-5m-6+56=0
We add all the numbers together, and all the variables
-5m+50=0
We move all terms containing m to the left, all other terms to the right
-5m=-50
m=-50/-5
m=+10
| 5-3y=11-4y | | 2x*2=3x+104 | | (1/15)-(7x)/5=21 | | 31=2g-4 | | 8s+2+s=58 | | 7x÷8-1÷4=4x÷5+11÷4 | | x6/3=1 | | 9x-3+4x=5 | | x+7=103 | | x-30.8=41.1 | | 7(x+2)=5(3x-1) | | x-53=23 | | 100=25c | | 4+5x=7+9 | | 22=a-5 | | -7-2x=-27 | | 21=4m+6 | | x+126=77 | | 3x+15+2x+2+2x-12=180 | | 6n+24=8 | | 5+4x+6=27 | | 5(6+3b)=5(4b+3) | | 6(x-6)=-12 | | 1/3x-2/5=-2x+3/2 | | 45x-48=250 | | s-17=35 | | ((2)/(5))x-6=-16 | | 2(m+1)=6. | | 4p+8=18 | | -2(-6n-6)=132 | | 5(x-1)-2=2(x+5)-x+3 | | 4(5-3x)+15=41 |